Identification of prevalence and antibiotic resistance property as a basis for establishing an efficient treatment of bacteria causing mastitis in beef cows - Hoang Diep Tran; Trong Ngu Nguyen (Veterinary Integrative Sciences, 2023)
The purpose of the study was to examine the occurrence of metritis on reproduction of beef cows. A total of 2,962 cows were examined, and samples were collected from those displaying clinical symptoms of bovine metritis for bacterial analysis. Bacterial species identification was performed using culture and PCR techniques. The findings revealed that bovine metritis affected 5.5% of the reproductive cow population with the presence of Streptococcus spp., Staphylococcus aureus, Escherichia coli, and Salmonella spp. at the rates of 87.7%, 61.1%, 59.9% and 17.3%, respectively. The results also demonstrated that Streptococcus spp. was the most prevalent group, while Salmonella spp. had the lowest prevalence across different breeds and litters. However, in the Limousin crossbred cows, the infection rate of E. coli surpassed that of the other bacteria and a significantly higher infection rate for E. coli was observed in litter 4 and litter ≥6 compared to the others. The disk diffusion method was utilized to assess antibiotic resistance patterns of the isolated bacteria. Among the bacteria, marbofloxacin exhibited the lowest prevalence of antibiotic resistance (16.9%), while doxycycline had the highest prevalence (82.2%). All cows recovered from the disease within 3-5 days of treatment, and all of them resumed estrus in the subsequent reproductive cycle. The pregnancy rate ranged from 66.7% to 80.0% for the first insemination in the next reproductive cycle.